Development and validation of a scale to measure team communication behaviors - Hartner-Tiefenthaler, Martina; Loerinc, Ivana; Hodzic, Sabina; Kubicek, Bettina (Frontiers in Psychology, 2022)
Introduction With the COVID-19 pandemic, remote work was increased all over the globe. As a consequence, workers had to adapt their communication behaviors to smoothly coordinate work in their flexible teams (i.e., when team members divide work between the office and their homes). Drawing on relational coordination theory, we constructed and validated a scale to capture the most relevant team communication behaviors. Methods We employed interviews and focus groups to construct the scale, refined the scale based on three samples with employees working flexibly and finally validated the scale with 130 teams from diverse organizations. Results Our scale comprises three dimensions: focused communication, knowledge sharing and spontaneous communication. All three dimensions showed convergent validity with team planning and discriminant validity with time-spatial flexibility. Also, predictive validity with collective efficacy and team viability was achieved for focused communication and knowledge sharing. Spontaneous communication only predicted collective efficacy, but not team viability. Discussion We conclude that the TCS is a reliable and valid measure for assessing team communication and contribute by focusing on behaviors.